APAKAH DIGITALISASI MEMITIGASI RISIKO PEMBIAYAAN PADA BANK SYARIAH SECARA GLOBAL? - Guntur Kusuma Wardana; Violinda Syahgaria Firdaus (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2026)
This study aims to examine the effect of profitability, liquidity, and technology on the financing risk of Islamic banks worldwide. The research is based on the global dynamics of financing risk, which ranges from 2.47% to 2, indicating a downward trend and reflecting an improvement in asset quality as well as the implementation of more prudent management. The method used is quantitative with a causality approach, analyzed through panel data regression using EViews 12 software. The results indicate that profitability has a significant effect on financing risk; liquidity (FDR) has a significant effect on financing risk; liquidity (QR) does not have a significant effect on financing risk; liquidity (CR) does not have a significant effect on financing risk; and technology does not have a significant effect on the financing risk of Islamic banks worldwide.